Free-choice high-fat diet consumption reduces lateral hypothalamic GABAergic activity, without disturbing neural response to sucrose drinking in mice - Slomp, Margo; Koekkoek, Laura L.; Mutersbaugh, Michael; Linville, Ian; Luquet, Serge H.; la Fleur, Susanne E. (Frontiers in Neuroscience, 2023)
Nutrition can influence the brain and affect its regulation of food intake, especially that of high-palatable foods. We hypothesize that fat and sugar have interacting effects on the brain, and the lateral hypothalamus (LH) is a prime candidate to be involved in this interaction. The LH is a heterogeneous area, crucial for regulating consummatory behaviors, and integrating homeostatic and hedonic needs. GABAergic LH neurons stimulate feeding when activated, and are responsive to consummatory behavior while encoding sucrose palatability. Previously, we have shown that glutamatergic LH neurons reduce their activity in response to sugar drinking and that this response is disturbed by a free-choice high-fat diet (fcHFD). Whether GABAergic LH neurons, and their response to sugar, is affected by a fcHFD is yet unknown. Using head-fixed two-photon microscopy, we analyzed activity changes in LHVgat neuronal activity in chow or fcHFD-fed mice in response to water or sucrose drinking. A fcHFD decreased overall LHVgat neuronal activity, without disrupting the sucrose-induced increase. When focusing on the response per unique neuron, a vast majority of neurons respond inconsistently over time. Thus, a fcHFD dampens overall LH GABAergic activity, while it does not disturb the response to sucrose. The inconsistent responding over time suggests that it is not one specific subpopulation of LH GABAergic neurons that is driving these behaviors, but rather a result of the integrative properties of a complex neural network. Further research should focus on determining how this dampening of LH GABAergic activity contributes to hyperphagia and the development of obesity.